Kontribusi Lingkungan Sosial (Orang Tua, Guru, Teman Sebaya) terhadap Academic Self-Regulation Siswa-Siswi Kelas X SMA ‘Y’Bandung - Jave Savitri; Heliany Kiswantomo; Hana Irawati Herawan (Provitae: Jurnal Psikologi Pendidikan, 2010)
This research is conducted to find out the contribution of social environment to the academic self-regulation of 10th grade students of SMA ‘Y’ Bandung. This research used social environment questionnaire based on the journal from Martinez-Pons (2002) and academic self-regulation based on Zimmerman’s theory (quoted in Boekaerts, 2000) among 160 people from SMA ‘Y’ Bandung. The result of this research showed that peers and teachers give a significant contribution to the academic self-regulation, while parents give a non-significant contribution to the academic self-regulation of the 10th grade students. The aspect of encouragement from parents, from teachers and the encouragement as well as the rewarding from peers give significant contributions to the academic self-regulation of the students. Keywords: social environment, academic self-regulation